Bahasa Arab - Holis; Fitria, Fitria; Rahmanita, Fatia; Bahruddin, Uril; Syifaussakinah (Tarling : Journal of Language Education, 2024)
This study aims to describe the Arabic language academy and Al Wasith Dictionary,the method of preparation and how to search for words in the Al Wasith dictionaryas well as its advantages and disadvantages. This research is a library researchusing a qualitative descriptive approach. The primary data source in the researchis the intermediary dictionary, and secondary sources are books, magazines,and other sources related to the field of dictionaries and research subjects. Datacollection was carried out using documentation technology, and the data wasanalyzed using the Miles and Huberman data model triangulation. The results ofthis study show that the Arabic language academy is not only limited to compiling dictionaries, but also includes participation in intellectual activities, researching linguistic issues, describing scientific and linguistic terminology, and organizingseminars in various locations. The purpose of compiling this dictionary is tocorrect and purify the Arabic language so that it can be easily understood. Theorder of words in the dictionary depends on alphabetical order. The way to searchfor a word is done by returning the word to its original form and removing theextra letters in the word. One of the advantages of this approach is that it usesverses from the Qur'an and the Prophet's hadith as reference and support inexplaining the words. The disadvantage is the difficulty of using Arabic for thosewho are not native speakers.